2015
DOI: 10.1002/ange.201503968
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Ligation and Isotope Labeling to Locate Dynamic Effects during Catalysis by Dihydrofolate Reductase

Abstract: Chemical ligation has been used to alter motions in specific regions of dihydrofolate reductase from E. coli and to investigate the effects of localized motional changes on enzyme catalysis.T wo isotopic hybrids were prepared;o ne with the mobile N-terminal segment containing heavy isotopes ( 2 H, 13 C, 15 N) and the remainder of the protein with natural isotopic abundance,and the other one with only the C-terminal segment isotopically labeled. Kinetic investigations indicated that isotopic substitution of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…3,4,37 Committor analysis also permits calculation of the barrier-crossing time for the hydride transfer reactions, which was the same for l- and h-DHFRs (Table 1). The computational data predict that ecDHFR is unlike other enzymes, 8-13 where altered enzyme mass has been demonstrated to influence the probability of barrier crossing. In ecDHFR, any vibrational motions altered by protein mass or temperature do not affect the TS or barrier-crossing parameters.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…3,4,37 Committor analysis also permits calculation of the barrier-crossing time for the hydride transfer reactions, which was the same for l- and h-DHFRs (Table 1). The computational data predict that ecDHFR is unlike other enzymes, 8-13 where altered enzyme mass has been demonstrated to influence the probability of barrier crossing. In ecDHFR, any vibrational motions altered by protein mass or temperature do not affect the TS or barrier-crossing parameters.…”
Section: Resultsmentioning
confidence: 93%
“…6,13 These investigations relied on steady-state k cat measurements at pH 9 and single-turnover kinetics at pH 7. It is unclear if the extracted kinetic constants reflect hydride transfer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have illustrated the importance of enzyme motions and have suggested the presence of networks of vibrational modes that enable conformational sampling of productive substrate binding and/or reaction geometries (e.g. refs ). Modulating such a network would then have the potential to tune enzyme activity without altering the fine detail of the electrostatic environment at the active site, which is the key requirement for catalysis.…”
Section: Resultsmentioning
confidence: 99%
“…Protein-based approaches offer the ability to function efficiently under mild reaction conditions. 5,6 Transferase, [13][14][15] oxidoreductase, [16][17][18] ligase, 19,20 transpeptidase 2,4,[21][22][23][24][25][26][27] and (split-)intein [28][29][30] have been applied for protein bioconjugation. Nevertheless, adapting these enzymes or proteins for synthetic applications, which deviate from their natural function, oen results in technical issues.…”
Section: Introductionmentioning
confidence: 99%